ENHANCING THE QUALITY OF BIO OIL FROM RICE STRAW WITH A COMBINATION OF CO-PYROLYSIS WITH PLASTIC AND CO-CATALYST Fe/Al2O3 - Sirait, Esterly Septiana; Anwar, Rangga Febry; Perwitasari, Dyah Suci; Puspitawati, Ika Nawang (JURNAL INTEGRASI PROSES, 2025)
This study investigates the enhancement of bio-oil quality derived from rice straw through co-pyrolysis with plastic waste (polypropylene and low-density polyethylene) and utilizing a Fe/Al₂O₃ co-catalyst. The pyrolysis process was conducted at 500°C for 20 minutes, with variations in plastic ratios and catalyst concentrations (0–20%). The results indicated that both the yield and calorific value of the bio-oil significantly increased with higher LDPE content and catalyst addition, achieving an optimum yield of 30.56% and a calorific value of 41.308 MJ/kg at a 0:50 PP:LDPE ratio with 20% catalyst. Viscosity and density values were also optimized, falling within ASTM standards with 2.511 cSt and 0.856 g/cm3. Gas chromatography-mass spectrometry (GC-MS) analysis confirmed the dominant presence of gasoline-range hydrocarbons and the absence of corrosive acetic acid. In contrast, ultimate analysis showed high carbon and hydrogen content, suggesting improved fuel quality. These findings indicate that combining co-pyrolysis with the Fe/Al₂O₃ catalyst and integrating plastic waste offers a promising method for producing high-quality, renewable bio-oil from rice straw.